Respiratory bronchiolitis associated interstitial lung disease (RB-ILD): a case of an acute presentation. Issue 10 (28th September 2004) - Mavridou, D; Laws, D
Abstract : Respiratory bronchiolitis associated interstitial lung disease (RB-ILD) is a recently described clinicopathological entity that occurs almost exclusively in current heavy cigarette smokers. Few cases have been reported in the literature and no studies have been carried out on the effect of treatment, which currently consists of smoking cessation with or without corticosteroids. We report the first case of an acute presentation of histologically proven RB-ILD in a young cigarette smoker whose diagnosis and management proved to be difficult. Smoking cessation alone was found to be inadequate so management was combined with corticosteroid therapy.